ANALISIS PENGETAHUAN IBU TENTANG METODE BERMAIN AKTIF DAN MEDIA BERMAIN SEDERHANA SEBAGAI EVALUASI KINERJA KADER POSYANDU DI DESA PAGONGAN - Riska Arsita Harnawati; Adevia Maulidya Chikmah (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2024)
Along with the development of technology, children prefer to spend time playing alone using game media called gadgets. Children who play with gadgets for 30 minutes increase their risk of being late in movement and speech by 49%. Cadres as implementers of posyandu activities have a large role in monitoring the growth and development of toddlers. Efforts that can be made by cadres as the spearhead of Posyandu are by disseminating knowledge about health, one of which is about children's growth and development. Cadres perform well in carrying out their duties as cadres. This is necessary to obtain accuracy in measurements and identify growth deviations, so that management can be carried out as early as possible to prevent stunting. This research aims to determine the knowledge of mothers of toddlers in stimulating development using active play methods and simple play media through evaluating the performance of posyandu cadres. The population in this study were mothers of toddlers in Pagongan Village who attended regular meetings at Posyandu. The instrument used in this research was a questionnaire containing the characteristics of respondents, knowledge of mothers of toddlers and measuring cadre performance. Quantitative data analysis uses descriptive analysis. The results obtained by mothers about active play methods and simple play media were less than 51 people (63.75%) and the majority of mothers assessed that the performance of cadres was still less active in conveying this information, namely 49 people (61.25%). The suggestion is that there needs to be a maximum role for cadres at the posyandu in providing information to mothers, as well as motivating mothers to continue bringing their children to the posyandu regularly.